Awaji criteria improves the diagnostic sensitivity in amyotrophic lateral sclerosis: A systematic review using individual patient data. Issue 7 (July 2016) - Geevasinga, Nimeshan; Loy, Clement T.; Menon, Parvathi; de Carvalho, Mamede; Swash, Michael; Schrooten, Maarten; Van Damme, Philip; Gawel, Malgorzata; Sonoo, Masahiro; Higashihara, Mana; Noto, Yu-ichi; Kuwabara, Satoshi; et al.
Highlights: Individual patient data analysis disclosed a higher sensitivity of the Awaji criteria when compared to the revised El Escorial criteria. Modification of Awaji criteria, to include a "possible" diagnostic category significantly enhanced the diagnosis of ALS, particularly in limb onset disease. Disease duration exerted a significant effect on the diagnostic utility of the Awaji criteria. Abstract: Objective: To determine the utility of the Awaji criteria in diagnosing amyotrophic lateral sclerosis (ALS) and to propose a novel modification so as to enhance sensitivity based on results of individual patient data (IPD). Methods: Individual patient data were available from 8 studies comparing the diagnostic accuracy of Awaji and revised El Escorial (rEEC) criteria. The sensitivity of a novel updated Awaji criteria, incorporating a "probable-laboratory supported" category, was also tested. Results: Individual patient data were available from 1086 patients, consisting of 881 ALS and 205 patients with disorders mimicking ALS. Summary sensitivities based on random effects logistic regression modelling disclosed a higher sensitivity of the Awaji criteria (0.70, 95% confidence interval [CI] 0.51–0.83) and updated Awaji criteria (0.73, 95% CI 0.56–0.85) when compared to rEEC (0.58, 95% CI 0.48–0.68). Paired analysis revealed higher sensitivities of Awaji criteria in 4 studies, and of updated Awaji criteria in 7 studies, when compared to rEEC. Conclusion: Individual patient data analysis established a higher sensitivity of Awaji criteria when compared to rEEC. The updated Awaji criteria enhanced the diagnostic sensitivity in limb-onset ALS. Significance: The updated Awaji criteria should be considered in clinical practice and future therapeutic trials.